2010
DOI: 10.3149/jms.1703.210
|View full text |Cite
|
Sign up to set email alerts
|

Homosexuality as a Risk Factor for Eating Disorder Symptomatology in Men

Abstract: Sexual orientation, body shame, body mass index (BMI), weight discrepancy and age were investigated as risks for eating disorder symptomatology in gay and heterosexual men (N = 230). Higher body shame (the dominant predictor) was associated with higher eating disorder symptomatology. Body shame appeared to be an expression of muscularity. BMI was the next strongest predictor, with heavier men reporting greater weight discrepancy, and in turn, eating disorder symptomatology. Overall, gay men were at greater ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 45 publications
1
25
0
2
Order By: Relevance
“…Body image concerns have been identified as the critical variable related to hazardous eating behaviours among gay men (Boisvert & Harrell, 2009;Strong et al, 2000). Body image satisfaction results from an evaluation process, and refers to one's beliefs about one's physical appearance (Cash, 2002).…”
mentioning
confidence: 99%
“…Body image concerns have been identified as the critical variable related to hazardous eating behaviours among gay men (Boisvert & Harrell, 2009;Strong et al, 2000). Body image satisfaction results from an evaluation process, and refers to one's beliefs about one's physical appearance (Cash, 2002).…”
mentioning
confidence: 99%
“…Research has shown that sexual orientation may have an effect on the prevalence of body image‐related issues among men. Results suggest that gay men are at greater risk for EDs than heterosexual men are (Boisvert & Harrell, 2009), with homosexuality/bisexuality shown as a specific risk factor in men who develop bulimia (Carlat et al, 1997). In addition, Siconolfi, Halkitis, Allomong, and Burton (2009) found that White and Latino gay men reported higher ED scores than did African American gay men.…”
Section: Common Symptoms and Risk Factorsmentioning
confidence: 99%
“…In addition, body image dissatisfaction negatively correlates with self-esteem and self-acceptance more strongly among gay males than among heterosexual males (Gil, 2007;Hunt, Gonsalkorale, & Nosek, 2012; Levesque & Vichesky, 2006;. Studies have also shown that within the male gay population, body image disturbances are strong predictors of eating disorders and restricted eating behaviour (Blashill, 2010;Boisvert & Harrell, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…However, mounting evidence has identified gay men as another potentially high-risk population (e.g., Feldman & Meyer, 2007;Russell & Keel, 2002). For instance, studies comparing gay and heterosexual men have found gay men experience and express more body image dissatisfaction (e.g., Morrison, Morrison, & Sager, 2004;Jankowski, Diedrichs, & Halliwell, 2014;Levesque & Vichesky, 2006), are more at risk of eating disordered symptomology (Boisvert & Harrell, 2009), and are more likely to meet the diagnostic criteria for an eating disorder (Russell & Keel, 2002). In addition, body image dissatisfaction negatively correlates with self-esteem and self-acceptance more strongly among gay males than among heterosexual males (Gil, 2007;Hunt, Gonsalkorale, & Nosek, 2012; Levesque & Vichesky, 2006;.…”
Section: Introductionmentioning
confidence: 99%